OTOMASI SISTEM KONTROLER ALAT PENGERING IKAN TERI (ENGKET BILEH) BERBASIS HYBRID ENERGY - Aljufri Aljufri; Abdul Rahman; Aditya Kamanurandi; Suci Indah Sari (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Anchoic dryer with automatic system based on Arduino UNO microcontroller using Hybrid Energy (a combination of solar energy with home electrical energy), designed to make it easier for fishermen to dry anchoic fish in all weathers. This research was conducted systematically starting from the process of making dryers equipped with solar panels and controller systems and shelves for drying of anchoateds made in portable form. Data collection testing is done by three methods, first using PLN electricity, second by combining PLN electricity and Solar Panel, Third Using Solar panels. The results of these three test processes show the percentage of ups and downs of moisture that occur in dryer shelves caused by the influence of unstable sunlight so that solar panels can not work properly resulting in the battery not storing current perfectly, so the system automatically switches to current. PLN electricity. Automation of the contoller system used in this dryer works well at the time of reading both at the temperature and humidity of the dryer room .